Enantioselective Syntheses of Yohimbine Alkaloids: Proving Grounds for New Catalytic Transformations - Miller, Eric R.; Scheidt, Karl A. (Synthesis, 2022)
The total synthesis of bioactive alkaloids is an enduring challenge and an indication of the state of the art of chemical synthesis. With the explosion of catalytic asymmetric methods over the past three decades, these compelling targets have been fertile proving grounds for enantioselective bond forming transformations. These activities are summarized herein both to highlight the power and versatility of these methods and to instill future inspiration for new syntheses of these privileged natural products.1 Introduction2 Monoterpenoid Indole Alkaloids2.1 Corynanthe-Type MIAs3 Biosynthesis4 Biological Activity5 Scope6 Strategies in Yohimbine Alkaloid Synthesis6.1 Momose’s Formal Synthesis of (+)-Yohimbine6.2 Jacobsen’s Synthesis of (+)-Yohimbine6.3 Hiemstra’s Synthesis of (+)-Yohimbine6.4 Qin’s Synthesis of (–)-Yohimbine6.5 Tan’s Synthesis of (+)-Rauwolscine6.6 Jacobsen’s Synthesis of (+)-Reserpine6.7 Chen’s Synthesis of (+)-Reserpine6.8 Riva’s Synthesis of (–)-Alloyohimbane6.9 Katsuki’s Synthesis of (–)-Alloyohimbane6.10 Ghosh’s Synthesis of (–)-Yohimbane and (–)-Alloyohimbane6.11 Hong’s Synthesis of (–)-Yohimbane6.12 Gellman’s Synthesis of (–)-Yohimbane6.13 Scheidt’s Synthesis of (–)-Rauwolscine and (–)-Alloyohimbane7 Conclusion
Keywords: asymmetric synthesis; asymmetric catalysis; alkaloids; total synthesis; catalysis